Bidirectional association between arterial and venous thrombosis - Lind, Caroline (UiT The Arctic University of Norway, 2017)
The papers II, III and IV of this thesis are not available in Munin. Paper II: Lind, C., Flinterman, L. E., Enga KF, Severinsen MT, Kristensen SR, Braekkan SK, Mathiesen EB, Njølstad I, Cannegieter SC, Overvad K, Hansen JB.: “Impact of incident venous thromboembolism on risk of arterial thrombotic diseases”. Available in Circulation 2014, 129(8):855-63. Paper III: Lind, C., Enga, K. F., Mathiesen, E. B., Njølstad, I., Brækkan, S. K., Hansen, J. B.: “ Family history of myocardial infarction and cause-specific risk of myocardial infarction and venous thromboembolism: the Tromsø Study”. Available in Circ Cardiovasc Genet. 2014, 7(5):684-91. Paper IV: Lind, C., Småbrekke, B., Rinde, L. B., Hindberg, K., Mathiesen, E. B., Johnsen, S. H., Arntzen, K. A., Njølstad, I., Lijfering, W., Brækkan, S. K., Hansen, J. B.: “Impact of venous thromboembolism on the formation and progression of carotid atherosclerosis: the Tromsø Study”. (Manuscript). Venous thromboembolism (VTE), a collective term for deep vein thrombosis (DVT) and pulmonary embolism (PE), has been considered a separate disease from arterial cardiovascular diseases (CVD, i.e. myocardial infarction (MI) and ischemic stroke). However, recent studies have proposed an association between VTE and arterial CVD. The aim of the thesis was to investigate this association in a general population. Papers I-III are prospective cohorts with participants from general populations (i.e. the Tromsø Study (papers I-III) and the Diet, Cancer and Health Study (paper II)). Paper IV is a matched cohort with participants attending ≥ 2 carotid ultrasounds in the Tromsø Study. Incident MI was associated with a transient increase in VTE risk, and a particularly high risk was found for PE during the first 6 months after MI. MI explained 6% of the PE events in the population. Incident VTE was associated with increased risk of future arterial CVD in all women and men < 65 years of age, and explained 1% of the arterial thrombotic events in the population. The risk of arterial CVD was ...